Small Fluxgate Magnetometers: Development and Future Trends in Spain - Lucas Pérez; Claudio Aroca; Marina Díaz-Michelena; David Ciudad (Sensors, 2010)
In this paper, we give an overview of the research on fluxgate magnetometers carried out in Spain. In particular we focus in the development of the planar-type instruments. We summarize the fabrication processes and signal processing developments as well as their use in complex systems and space.